Cat in the crypt - Baglio, Ben M. (New York : Scholastic, 1999)
At Animal Ark, Mandy Hope helps her parents treat animals of all shapes and sizes. Even outside the clinic, Mandy can't resist helping any animal in need and sometimes even ghostly animals need her assistance. Mandy helps solve the disappearance of a cat called Bathsheba.
"A Working Partners Book"--P. [4] of cover.
"An Apple paperback".
Ages 8 to 11.
Grade 4.
Keywords: Animal welfare -- Juvenile fiction; Cats -- Juvenile fiction; Animal ghosts -- Juvenile fiction; Veterinary hospitals -- Juvenile fiction; General fiction